Post-East Asian Financial Crisis: Challenges and Opportunities for the Banking and Financial Services Sector in Singapore - Fock, Siew Tong (Institutional Knowledge at Singapore Management University, 2001)
The East Asian financial crisis revealed the structural weaknesses of the banking systems in Asia. Post crisis, there were signs of limited recovery of the region in sight, but the region-wide reforms would take some time to complete. This paper identifies the main challenges and opportunities that are posed to the financial sector in Singapore in a post East Asian financial crisis scenario. Preserving the stability of the banking sector whilst engendering a more efficient use of capital remains a central issue in this paper. The paper also evaluates the liberalization measures adopted by the Monetary Authority of Singapore to enhance the development of Singapore as a leading international financial center.